Premature mortality: Europe’s persisting Iron Curtain? - Zatoński, Mateusz; Zatoński, Witold; Wojtyła, Andrzej (Journal of Health Inequalities, 2016)
One of the chief arguments of advocates of European Union (EU) accession in Central and Eastern Europe (CEE) was that EU membership will help CEE states to catch up with the more developed Western European countries. The economic and technological chasm that existed between the two parts of the continent was closely echoed by the enormous gap in premature adult mortality levels. This health gap was present throughout the 20th century. Intensive efforts to control infectious diseases in the Soviet bloc allowed the life expectancy figures of CEE states to almost catch up with the West in the 1960s, but in the subsequent decades the health gap widened again. This was largely due to the man-made disease epidemic that engulfed the CEE region as a result of over-medicalisation of health, persisting low levels of health literacy, and unhealthy lifestyles (high levels of smoking and alcohol consumption, poor diets). The collapse of communist regimes in 1989 and the following years led to another change in health trends in CEE countries. Antiquated models of healthcare were abandoned, market economy helped precipitate positive changes in diet, a reduction in smoking and alcohol consumption were observed in many countries. However, even after 25 years of improvement, health in CEE countries remains significantly behind Western Europe, and while huge advances have been made in some areas in many countries (e.g. tobacco control), there is still much to be done in others (e.g. limiting alcohol consumption). Currently, three distinct health zones can be identified in Europe. The first is Western Europe, where mortality before 65 in many countries is in single-digit figures. The second are the CEE countries, where one if three men die before the age of 65. The third is Russia and the former Soviet states, where over half of all men do not life to the age of 65.